Oleanolic acid enhances tight junctions and ameliorates inflammation in Salmonella typhimurium-induced diarrhea in mice via the TLR4/NF-κB and MAPK pathway. Issue 1 (11th December 2019) - Dong, Na; Xue, Chenyu; Zhang, Lei; Zhang, Tingting; Wang, Chensi; Bi, Chongpeng; Shan, Anshan
Abstract : Oleanolic acid attenuates intestinal inflammation and intestinal tight junction barrier damage through the TLR4/NF-κB and MAPKs pathway. Abstract : Salmonella typhimurium ( S.T ) is a common cause of acute, self-limiting food-borne diarrhea with severe intestinal inflammation and intestinal barrier damage. Oleanolic acid (OA), isolated from almost 2000 plant species, has been shown to have anti-inflammatory roles. The purpose of this study was to investigate the potential protective effects of OA on S.T -induced diarrhea and enteritis and to elucidate its anti-inflammatory mechanisms. A total of eighty BALB/c mice (4-week-old) were randomly divided into the control group (no S.T, no OA), the S.T group ( S.T only), the S.T + OA group ( S.T plus 100 mg kg −1 OA) and the OA group (100 mg kg −1 OA only). Compared with the S.T group, OA administration significantly reduced clinical symptoms and weight loss, and the severity of diarrhea and intestinal structural damage was significantly alleviated, which was confirmed by a decrease in the diarrhea index (DI) and jejunal histological damage. In addition, in the infected jejunum, OA maintained the expression and localization of occludin, claudin-1 and ZO-1 to protect the jejunal barrier, thereby maintaining the integrity of the gut barrier. Finally, OA treatment not only reduced the levels of COX-2 and iNOS but also inhibited the secretion of pro-inflammatory cytokines, such as IL-1β, IL-6 and TNF-α. Furthermore, western blotting results showed that OA treatment significantly inhibited IκB phosphorylation and degradation in intestinal tissues and the nuclear translocation of p65, and OA also decreased the level of TLR4 and the activation of the MAPK pathway. To summarise, OA can maintain the intestinal tight junction barrier and prevent diarrhea caused by S.T . as well as reduce intestinal inflammation through the NF-κB and MAPK signaling pathways.